Biosynthesis of lactacystin as a proteasome inhibitor - Takeshi Tsunoda; Shunkichi Furumura; Haruka Yamazaki; Chitose Maruyama; Yoshimitsu Hamano; Yasushi Ogasawara; Tohru Dairi (Communications Chemistry)
Abstract Lactacystin is an irreversible proteasome inhibitor isolated from Streptomyces lactacystinicus. Despite its importance for its biological activity, the biosynthesis of lactacystin remains unknown. In this study, we identified the lactacystin biosynthetic gene cluster by gene disruption and heterologous expression experiments. We also examined the functions of the genes encoding a PKS/NRPS hybrid protein (LctA), NRPS (LctB), ketosynthase-like cyclase (LctC), cytochrome P450 (LctD), MbtH-like protein (LctE), and formyltransferase (LctF) by in vivo and in vitro experiments. In particular, we demonstrated that LctF directly transferred the formyl group of 10-N-formyl tetrahydrofolate to CoA. The formyl group of formyl-CoA was then transferred to ACP1 by LctA_AT1 to form formyl-ACP1. This is the first example of an AT domain recognizing a formyl group. The formyl group is perhaps transferred to methylmalonate tethered on LctA_ACP2 to yield methylmalonyl-semialdehyde-ACP2. Then, it would be condensed with leucine bound to PCP in LctB by the C domain in LctA. Using a mimic compound, we confirmed that LctC catalyzed the formation of the cyclic α,α-disubstituted amino acid structure with concomitant release of the product from PCP. Thus, we figured out the overall biosynthesis of lactacystin including a novel role of a formyl group in a secondary metabolite.